2018
DOI: 10.1101/244467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revisiting the functional properties of NPF6.3/NRT1.1/CHL1 in xenopus oocytes

Abstract: Within the Arabidopsis NPF proteins, most of the characterized nitrate transporters are low-affinity transporters, whereas the functional characterization of NPF6.3/NRT1.1 has revealed interesting transport properties: the transport of nitrate and auxin, the eletrogenicity of the nitrate transport and a dual-affinity transport behavior for nitrate depending on external nitrate concentration. However, some of these properties remained controversial and were challenged here. We functionally express WT NPF6.3/NRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The findings of Wang et al, [17] and Liu et al, [18] have shown that over 75% of high-affinity nitrate uptake in plants (calculated by subtracting the root nitrate uptake rate of nrt1.1 mutants from that of wild-type plants) was contributed by NRT1.1. However, several studies have questioned the contribution made by the NRT1.1 high-affinity function to nitrate uptake with low external nitrate concentrations [21,22]. However, several studies have questioned the contribution made by the NRT1.1 high-affinity function to nitrate uptake with low external nitrate concentrations [21,22].…”
Section: Nitrate (No àmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of Wang et al, [17] and Liu et al, [18] have shown that over 75% of high-affinity nitrate uptake in plants (calculated by subtracting the root nitrate uptake rate of nrt1.1 mutants from that of wild-type plants) was contributed by NRT1.1. However, several studies have questioned the contribution made by the NRT1.1 high-affinity function to nitrate uptake with low external nitrate concentrations [21,22]. However, several studies have questioned the contribution made by the NRT1.1 high-affinity function to nitrate uptake with low external nitrate concentrations [21,22].…”
Section: Nitrate (No àmentioning
confidence: 99%
“…Soon after this study, analysis of the nitrate uptake activity in NRT1.1-injected Xenopus oocytes showed that NRT1.1 had both high-and low-affinity nitrate uptake kinetic features, where the shift in affinity was associated with a phosphorylation event on the T101 residue of the NRT1.1 protein [17][18][19][20], providing further evidence that NRT1.1 acts as both a HAT and a LAT. However, several studies have questioned the contribution made by the NRT1.1 high-affinity function to nitrate uptake with low external nitrate concentrations [21,22]. For example, Touraine and Class [23], Muños et al [24], and Remans et al [25] failed to detect reduced HATS influxes in nrt1.1 mutants in low KNO 3 growth medium (compared with wild-type plants) when these plants were precultured with KNO 3 or 1 mM NH 4 NO 3 .…”
mentioning
confidence: 99%
“…In our hands, NRT1.4 was electrically silent in oocytes, which could be due to electroneutral nitrate/proton symport by NRT1.4. Chiu et al (2004) reported NRT1.4-dependent nitrate-inward currents by the two-electrode voltage-clamp (TEVC) method, but technical glitches when measuring nitrate fluxes by TEVC in Xenopus oocytes have been reported (Noguero et al, 2018). In summary, our results demonstrate that CIPK23 phosphorylates NRT1.4 at Thr98, and that this modification reduces the transport rate of NRT1.4 in the low-affinity range.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, these results are confirmed by the high expression of the BnNRT2.1 gene at low nitrate concentrations and the velocities ratio v app / v out in 15 N fluxes which reveals an increase in one order magnitude in transporters activity from 0.28 (stationary state) to 0.01 mM of external nitrate concentrations ( Figure 6C ). Moreover, a recent study of the functional properties of NPF6.3/NRT1.1 in xenopus ovocytes suggests that the nitrate influx and efflux by this transporter are also controlled by changes in endogenous nitrate concentrations ( Noguero et al, 2018 ). Finally, application of external Glu to uncouple NRT2.1 from NPF6.3/NRT1.1 at the transcriptional and activity levels (exp3) indicated that the NRT2.1 transporter is essential for nitrate translocation and osmotic water flux required for shoot growth in response to nitrate availability.…”
Section: Discussionmentioning
confidence: 99%